2015
DOI: 10.1016/j.cmi.2014.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of KPC-producing Enterobacteriaceae: suboptimal efficacy of polymyxins

Abstract: Treatment of Klebsiella pneumoniae carbapenemase-producing Enterobacteriaceae infections (KPC-EI) remains a challenge. Combined therapy has been proposed as the best choice, but there are no clear data showing which combination therapy is superior. Our aim was to evaluate the effectiveness of antimicrobial regimens for treating KPC-EI. This was a retrospective cohort study of KPC-EI nosocomial infections (based on CDC criteria) between October 2009 and June 2013 at three tertiary Brazilian hospitals. The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 20 publications
3
43
0
3
Order By: Relevance
“…CRE resistance to colistin has been reported in several countries in the last years [47] and infections caused by these bacteria are associated with high mortality [8–10]. KPC is the most frequent carbapenemase described in Enterobacteriaceae in Brazil with great mortality [8, 11]. One cohort study in Brazil described 118 patients with CRE infections in a period of almost four years.…”
Section: Introductionmentioning
confidence: 99%
“…CRE resistance to colistin has been reported in several countries in the last years [47] and infections caused by these bacteria are associated with high mortality [8–10]. KPC is the most frequent carbapenemase described in Enterobacteriaceae in Brazil with great mortality [8, 11]. One cohort study in Brazil described 118 patients with CRE infections in a period of almost four years.…”
Section: Introductionmentioning
confidence: 99%
“…Colistin has become the most popular agent for the treatment of infections due to K. pneumoniae with carbapenemases (101,102). Colistin monotherapy has been associated with mortality rates exceeding 50% when used for severe infections (111), and one Brazilian study showed that combination therapy was not superior to monotherapy (112). Recent understanding of the pharmacokinetics of colistin has resulted in the use of doses higher than those used in early studies.…”
Section: Treatment Of Infections Due To K Pneumoniae With Carbapenemmentioning
confidence: 99%
“…Data are available to support the use of combination therapy for the treatment of serious infections (10,11); however, these benefits may primarily be limited to those patients with severe underlying conditions (12). Collectively, inclusion of a carbapenem in the treatment of carbapenemaseproducing Enterobacteriaceae appears to be associated with lower mortality rates compared to carbapenem-sparing treatment regimens, but this has not been borne out in all observational studies (13). Without unequivocal outcome data supporting the 2010 CLSI and EUCAST guidelines, physicians may be reluctant to treat CP-CRE with a susceptible carbapenem.…”
mentioning
confidence: 99%